2016
DOI: 10.1161/circulationaha.116.022415
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Epidural Anesthesia Reduces Right Ventricular Systolic Function With Maintained Ventricular-Pulmonary Coupling

Abstract: URL: http://www.trialregister.nl/trialreg/admin/rctview.asp?TC=2844. Unique identifier: NTR2844.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 54 publications
0
20
0
1
Order By: Relevance
“…40 Beyond the aforementioned potential causes, loss of the substantial innervation of the RV myocardium may be an other important factor resulting in complex functional changes of the RV. 41 However, it has been suggested that the transplanted heart can be reinnervated by both sympathetic and parasympathetic fibers. 42,43 Hypothetically, the slow recovery of longitudinal function can be a result of reinnervation as well.…”
Section: Discussionmentioning
confidence: 99%
“…40 Beyond the aforementioned potential causes, loss of the substantial innervation of the RV myocardium may be an other important factor resulting in complex functional changes of the RV. 41 However, it has been suggested that the transplanted heart can be reinnervated by both sympathetic and parasympathetic fibers. 42,43 Hypothetically, the slow recovery of longitudinal function can be a result of reinnervation as well.…”
Section: Discussionmentioning
confidence: 99%
“…15 Homeometric autoregulation describes maintenance of RV systolic function in response to elevated pulmonary vascular resistance (PVR), an intrinsic adaptation that enables the RV to maintain stroke volume without having to depend on the Frank-Starling mechanism. 16 However, intraoperative interventions that either compromise RV homeometric autoregulation (e.g. sympathetic block such as spinal anaesthesia, thoracic epidural, vasovagal stimuli, or anaesthetic drugs with a negative inotropic effect) or that disproportionately decrease the compliance in small pulmonary vessels (e.g.…”
Section: Pathophysiology Of Perioperative Rv Failurementioning
confidence: 99%
“…23,59 An increase in CVP with systemic hypotension often indicates the onset of RV failure and circulatory collapse. 16 The choice of advanced monitoring such as pulmonary artery catheter, transpulmonary dilution (i.e. LiDCO, PiCCO), or transoesophageal echocardiography (TOE) depends on local availability/expertise.…”
Section: Perioperative Monitoringmentioning
confidence: 99%
“…Table 1 summarises clinical studies in which conductance catheters were used to assess contractility and/or RV–arterial coupling. The studies included patients with PAH (Tello et al, 2019), idiopathic or systemic sclerosis‐associated PAH (Tedford et al, 2013; Hsu et al, 2016), systemic sclerosis without pulmonary hypertension (Tedford et al, 2013), chronic thromboembolic pulmonary hypertension (CTEPH; McCabe et al, 2014; Axell et al, 2017; Tello et al, 2019), chronic thromboembolic disease without pulmonary hypertension (McCabe et al, 2014; Axell et al, 2017), tetralogy of Fallot (Latus et al, 2013), and heart failure with preserved ejection fraction (EF; Rommel et al, 2018), as well as patients undergoing lung resection (Wink et al, 2016). The main difference between these studies is the method used to assess RV–arterial coupling.…”
Section: Assessment Of Rv Contractile Function and Rv–arterial Couplingmentioning
confidence: 99%
“…In four of the studies (Latus et al, 2013; Tedford et al, 2013; Hsu et al, 2016; Rommel et al, 2018), E es was measured using a multi‐beat method (Figure 1) with preload reduction either by balloon occlusion of the inferior vena cava or through the Valsalva manoeuvre (first shown to significantly reduce RV preload in 2013, Wang et al, 2013, and validated for multi‐beat measurement of pressure–volume loops using inferior vena cava balloon occlusion, Tedford et al, 2013). In the remaining four studies (McCabe et al, 2014; Wink et al, 2016; Axell et al, 2017; Tello et al, 2019), the conductance catheter was used to measure precisely the ESP as one of the essential values required for determination of coupling via the single‐beat method (Brimioulle et al, 2003). In the single‐beat method, E a is calculated as ESP/SV and E es is calculated as ( P max − ESP)/SV, where P max is estimated as the maximal theoretical pressure that would build up through clamping of the pulmonary valve.…”
Section: Assessment Of Rv Contractile Function and Rv–arterial Couplingmentioning
confidence: 99%